Inhibition of Pancreatic Lipase by Flavonoid Derivatives: In Vitro and In Silico Investigations - The-Huan Tran; Thanh-Tan Mai; Thi-Thu-Trang Ho; Thi-Ngoc-Dung Le; Thi-Cam-Nhung Cao; Khac-Minh Thai; Thai-Son Tran (Advances in Pharmacological and Pharmaceutical Sciences)
Obesity, characterized by excessive adipose tissue accumulation, has emerged as a crucial determinant for a wide range of chronic medical conditions. The identification of effective interventions for obesity is of utmost importance. Widely researched antiobesity agents focus on pancreatic lipase, a significant therapeutic target. This study presented the evaluation of ten flavonoid compounds in terms of their inhibitory activities against pancreatic lipase, utilizing both in vitro and in silico approaches. The results indicated that all tested compounds demonstrated modest and weaker inhibitory activities compared to the reference compound, orlistat. Among the compounds investigated, F01 exhibited the highest potency, with an IC50 value of 17.68 ± 1.43 µM. The enzymatic inhibition kinetic analysis revealed that F01 operated through a competitive inhibition mechanism with a determined Ki of 7.16 μM. This value suggested a moderate binding affinity for the pancreatic lipase enzyme. Furthermore, the associated Vmax value was quantified at 0.03272 ΔA·min−1. In silico studies revealed that F01 displayed a binding mode similar to that of orlistat, despite lacking an active functional group capable of forming a covalent bond with Ser152 of the catalytic triad. However, F01 formed a hydrogen bond with this crucial amino acid. Furthermore, F01 interacted with other significant residues at the enzyme’s active site, particularly those within the lid domain. Based on these findings, F01 demonstrates substantial potential as a candidate for further investigations.